Transitional changes in the CRP structure lead to the exposure of proinflammatory binding sites - David Braig (Nature Portfolio, 2017)
C-reactive protein is a pentameric protein secreted by the liver in response to injury and infection. Here Braiget al. show that conformational changes in CRP on the surface of monocyte-derived microvesicles enable binding of complement C1q and lead to activation of the complement cascade and aggravation of inflammation.